Spatial variation in groundwater depletion across China under multiple stresses - Lin, Xuemin; Li, Weifeng; Bai, Xueding; Han, Lijian; Ming, Dongping (Frontiers in Environmental Science, 2022)
Groundwater, an essential component of the hydrological cycle, has been subject to intense pressure worldwide over recent decades, such that reserves have changed appreciably, challenging our ability to deliver on water resource protection goals. While the changes in storage can be quantified, there is little information about what drives the changes in groundwater storage (GWS) and how the impacts of those drivers vary spatially and temporally. In this study, the spatial and temporal variations in GWS across China from 2002 to 2016 is studied, and it is examined how GWS was influenced by natural and anthropogenic drivers at multiple scales using Gravity Recovery and Climate Experiment (GRACE) satellite data. The national-scale GWS declined continuously at a rate of −0.27 cm/a over the study period. Interesingly, the difference in the GWS change between the south (increasing) and the north (decreasing) was decreasing, while the gap between the east (increasing) and the west (decreasing) was becoming wider. The main drivers of GWS changes at the national and regional scales were precipitation, agricultural water consumption, and the total population, while industrial water consumption, domestic water consumption, and evapotranspiration were important at the regional and provincial scales. Policies recently implemented to protect GWS have been effective. Given the potential for GWS changes to have impacts at multiple scales, policies and goals should address the drivers of GWS changes at different scales.